Sistem Informasi Manajemen E-Budidaya CV.Tarkiz Paz Banua - Fariza, Reihan; Norkhalis, Emha (Journal Information Technology Trends (JITRENDS), 2024)
The development of information technology has had a significant impact on various sectors,including animal husbandry. Livestock sustainability requires effective and inexpensive solutions.This research was born in response to a request from livestock sector operators to the softwarehouse company CV.Tarkiz Paz Banua to develop an E-Budidaya management information system.The aim of the close collaboration between software companies and livestock sector operators isto increase the affordability of livestock operations, with a focus on providing food and medicineto livestock. This research involves designing and developing an E-Budidaya management systemthat facilitates product sales, and ensures quick access to product information. By utilizing digitaltechnology, it is hoped that the ordering, payment and product delivery processes can be carriedout efficiently, thereby increasing customer satisfaction and strengthening business relationshipsbetween partners and operators in the livestock sector. The E-Budidaya management informationmanagement system also provides the latest information on livestock products, includinginstructions for use, nutritional composition and dosage recommendations, thereby increasingagricultural knowledge and providing added value to the company's products. This study reflectsthe contribution of positive collaborative innovation between software companies and livestock companies through effective digital solutions that improve operational efficiency, customerservice and product added value in narrow markets.